2021
DOI: 10.1097/htr.0000000000000714
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive Dizziness Among Post-9/11 Veterans With Deployment-Related Traumatic Brain Injury

Abstract: Objective: To identify disruption due to dizziness symptoms following deployment-related traumatic brain injury (TBI) and factors associated with receiving diagnoses for these symptoms. Setting: Administrative medical record data from the Department of Veterans Affairs (VA). Participants: Post-9/11 veterans with at least 3 years of VA care who reported at least occasional disruption due to dizziness symptoms on the comprehensive TBI evaluation. Design: A cross-sectional, retrospective, observational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…73,74 The vestibular subscale may not be sensitive enough to independently measure vestibular function as it consists of three subjective symptoms: dizziness, clumsiness, and loss of balance. There are few studies examining the validity of this subscale, 75 whereas no data exist regarding comparison to the "gold standard" (ie, caloric testing). 73…”
Section: Study Limitationsmentioning
confidence: 99%
“…73,74 The vestibular subscale may not be sensitive enough to independently measure vestibular function as it consists of three subjective symptoms: dizziness, clumsiness, and loss of balance. There are few studies examining the validity of this subscale, 75 whereas no data exist regarding comparison to the "gold standard" (ie, caloric testing). 73…”
Section: Study Limitationsmentioning
confidence: 99%
“…Swan et al examined factors impacting whether or not veterans with dizziness symptomatology received a diagnosis of dizziness versus a vestibular disorder. They found that black veterans had significantly reduced odds of receiving a vestibular disorder diagnosis when compared to white individuals 21 . Another recent study by Souza et al 22 examined geographic variation in the care of patients with a vestibular disorder and found that location impacted management.…”
Section: Key Action Statement Strength Of Recommendationamentioning
confidence: 99%
“…They found that black veterans had significantly reduced odds of receiving a vestibular disorder diagnosis when compared to white individuals. 21 Another recent study by Souza et al 22 examined geographic variation in the care of patients with a vestibular disorder and found that location impacted management. Despite these newer studies and a call to increase research investigating variations in care for BPPV, there have been no further studies investigating whether there are sociodemographic variations in the diagnosis or management of dizziness etiology such as BPPV.…”
mentioning
confidence: 99%